2019
DOI: 10.1016/bs.ircmb.2018.07.006
|View full text |Cite
|
Sign up to set email alerts
|

T Lymphocytes as Measurable Targets of Protection and Vaccination Against Viral Disorders

Abstract: Continuous epidemiological surveillance of existing and emerging viruses and their associated disorders is gaining importance in light of their abilities to cause unpredictable outbreaks as a result of increased travel and vaccination choices by steadily growing and aging populations. Close surveillance of outbreaks and herd immunity are also at the forefront, even in industrialized countries, where previously eradicated viruses are now at risk of re-emergence due to instances of strain recombination, contract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 518 publications
(508 reference statements)
0
2
0
Order By: Relevance
“…Cellular immunity are integrally linked during the initial induction of immunity against pathogens, these can become disconnected with developing pathology. This loss of correlation between T cells and neutralizing antibody responses varies according to different viruses, suggesting that independent time course measures of these separate immune responses are required over time for adequate recording of biomarkers of natural infection and vaccine efficacy or suggesting that T cell status may be most crucial measure of conferred long-term immunity( Monette and Mouland, 2019 ). The understanding of such immunological parameters in respiratory viral infections, clinical diagnostic models, and disease understanding may be refined.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular immunity are integrally linked during the initial induction of immunity against pathogens, these can become disconnected with developing pathology. This loss of correlation between T cells and neutralizing antibody responses varies according to different viruses, suggesting that independent time course measures of these separate immune responses are required over time for adequate recording of biomarkers of natural infection and vaccine efficacy or suggesting that T cell status may be most crucial measure of conferred long-term immunity( Monette and Mouland, 2019 ). The understanding of such immunological parameters in respiratory viral infections, clinical diagnostic models, and disease understanding may be refined.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the special immunological condition reported during physiological pregnancy, evidencing the importance of specific immune-regulatory processes, in which a crucial role belongs to the major histocompatibility complex molecules, in humans HLAs (Human Leukocyte Antigens), which are also involved in the response against viral infections [ 47 , 48 ]. The loss or down-regulation of classical HLA class-Ia antigens, as well as the neo-expression of non-classical HLA class-Ib antigens (HLA-E, -F, and -G), is a frequent strategy used by viruses for evading immune surveillance [ 49 , 50 , 51 ]. Among these non-classical HLA-Ib molecules, HLA-G and HLA-E represent the most studied for their tolerogenic role toward the fetus during pregnancy [ 52 ] and for their regulating function in neoangiogenesis during placentation [ 53 ].…”
Section: Methodsmentioning
confidence: 99%